Expected benefits of administration of tannins extracted from Acacia seyal plants; a biochemical and traditional medicine overview - M. I, Abdelgadir (International Journal of Scientific World, 2023)
This study was focused on expected benefits of administration of tannins extracted from Acacia seyal pants. Tannins have been used throughout history for their pharmacological properties as part of plants and herbs in traditional medicine. Tannins are a heterogeneous group of polyphenols, secondary metabolites in plants synthesized in response to biotic and abiotic stress inducers. The phenolic rings and hydroxyl groups present in their chemical structures confer them antioxidant and protein-binding properties. Study results clearly showed the presence of tannins significantly (p≤0.05) in Acacia seyal plants, compared to control. There are many sources of tannins. Tannins, which are of great importance in traditional medicine can be extracted from numerous trees and small bushes rich in tannins.